Analisis Faktor-Faktor yang Mempengaruhi Peningkatan Kunjungan Wisatawan yang Berdampak pada Pengembangan UMKM Implikasinya pada Penciptaan Lapangan Kerja dan Penerimaan Daerah DKI Jakarta - Endah Marendah Ratnaningtyas (EBBANK, 2019)
The research objective was to study and analyze the relationship amongtourism  activities   (security  and macro  economics policy,   tourism  budgetpolicy, development  strategy   of   tourism object  destination,   developmentstrategy   of   supporting   facilities,   programs   of   stays).   Specifically,   theresearch   analyzed   the   degree   of   either   partial   or   simultant   impacts   oftourism   activities   to   domestic   and   foregin   tourism   visits,   the   degree   ofeither partial or simultant impacts of domestic and foreign tourism visits onthe development of  micro, small, middle industries, the degree of eitherpartial   or   simultant   impacts   the   development   of  micro,   small,   middleindustries  on job creation and regional revenue of tourism sector in DKI Jakarta. The research was conducted in DKI Jakarta in 2018.The research population was of corporation of tourism sector adding up to 350   institution,   consisting   of   120   travel   agencies,   70   hotels   and   160restaurants.   The   research   sample   was   collected   through  propotionalestratified random sampling  and was determined to  172 corporations (big,middle   and   small).   This   research   also   used   secondary   data   from   DKI Jakarta   Tourism   Agency,   Association   of   Indonesia   Tourism   &   TravelAgency (ASITA), Association of Indonesia Hotel and Restaurant Agency (APHRI) in the form of time series data ranging from since 2008 to 2018.This research used descriptive analysis as well as inferential. The researchtype was of explanatory research through which path anaysis was appliedto explain the degrees of direct and indirrect contribution among variables.To   support   the   efficiency   and   accurate   of   data   processing,   statisticalsoftware, SPSS Ver 23 was used. The results of this research brought about implication that there was aneed to create good business climate supported by policy and regulation, tourism information centre, human resources quality improvement and thedevelopment of  micro,  small, middle  industries  capital aid.  Besides, thebusiness network development, tourism support participation, improvementof tourism workers welfare and good cooperation among other provinciesin  Indonesia  are some   necessary aspects  to consider  when  developingnational tuorism industries.